Pragmatic Instructions in Oral Communication in Context - Joseph B Quinto (Universitas Islam Ahmad Dahlan (UIAD), 2024)
There is a need to revisit and recalibrate pragmatic instructions of English teachers in the Philippines to adequately communicate the competencies required of students. Consequently, the primary purpose of this research was to look into the pragmatic instructions utilized by senior high school English teachers and whether there was a difference in the use of their pragmatic instructions when grouped according to years of service and educational attainment in one leading private senior high school in Baguio City, Philippines. By employing a survey questionnaire and a series of classroom observations of all senior high school English teachers, the researcher found that they sometimes integrated at least one from instructional pragmatic approaches and at least one from interlanguage pragmatic awareness-raising techniques, interlanguage pragmatic communicative practice techniques, interlanguage pragmatic corrective feedback techniques, and culture teaching techniques in every lesson in their Oral Communication in Context classes. Meanwhile, there was a discrepancy between the perceptions of English teachers as expressed in the questionnaire and their performance in the classroom. Although there were generally no significant differences in the application of pragmatic instructions by English teachers when grouped according to years of service and educational attainment, there is sufficient evidence to suggest that they incorporate more approaches and more techniques as they amass more years in the English teaching profession as well as when they obtain more advanced degrees in the graduate school. Besides adding to the body of literature regarding pragmatic instructions, this research endeavor also puts forward recommendations for future study.